Executive Stock Options as Mixed Gambles: Revisiting the Behavioral Agency Model - Martin, Geoffrey P.; Gomez-Mejia, Luis R.; Wiseman, Robert M. (Academy of Management Journal, 2013)
Conceiving of stock options as providing CEOs with cues for the possibility of both greater prospective wealth and losses to current wealth, we revisit predictions of the behavioral effects of equity-based pay using the behavioral agency model (BAM). We refine the BAM's original formulation and provide an explanation for previous conflicting empirical results by theorizing that the anticipation of prospective wealth attenuates the negative effect of accumulated current equity wealth upon CEO strategic risk taking. In doing so, we offer an advancement of the dialectic between: (1) classical agency scholars, arguing that equity-based pay leads to more risk taking, and (2) behavioral scholars, arguing that equity wealth creates risk bearing, leading to less risk taking. We also suggest that the influences of prospective wealth and current wealth on strategic risk taking depend on the extent to which agents can manage the risk inherent in their compensation package and agent vulnerability to losses. Formal hypotheses to test these expectations are made by focusing on equity-based compensation. Our findings offer strong support for these theoretical expectations.